2013
DOI: 10.1002/2013sw000995
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of galactic cosmic rays and lunar proton “albedo” to dose and dose rates near the Moon

Abstract: [1] We use validated radiation transport models of the Cosmic Ray Telescope for the Effects of Radiation instrument and its response to both primary galactic cosmic rays (GCR) and secondary radiation, including lunar protons released through nuclear evaporation, to estimate their relative contributions to total dose rate in silicon (372 μGy/d) and dose equivalent rate at the skin (2.88 mSv/d). Near the Moon, we show that GCR accounts for~91.4% of the total absorbed dose, with GCR protons accounting for~42.8%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…The results of this analysis show that declining solar activity and the subsequently weakening heliospheric magnetic field in the protracted solar cycle 23-24 minimum leads to an increasingly hazardous radiation environment due to elevated fluxes of galactic cosmic rays. We project out to the cycle 24-25 solar minimum and find an elevated dose equivalent rate of ∼0.3 cSv/d in interplanetary space behind 16 g/cm 2 nominal spacecraft shielding or equivalently ∼ 0.15 cSv/d on the lunar surface where roughly half of the incident radiation is blocked by the Moon [Spence et al, 2013]. The estimate for interplanetary space is in reasonable agreement with a previous estimate made for similar shielding by Mewaldt et al [2005].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this analysis show that declining solar activity and the subsequently weakening heliospheric magnetic field in the protracted solar cycle 23-24 minimum leads to an increasingly hazardous radiation environment due to elevated fluxes of galactic cosmic rays. We project out to the cycle 24-25 solar minimum and find an elevated dose equivalent rate of ∼0.3 cSv/d in interplanetary space behind 16 g/cm 2 nominal spacecraft shielding or equivalently ∼ 0.15 cSv/d on the lunar surface where roughly half of the incident radiation is blocked by the Moon [Spence et al, 2013]. The estimate for interplanetary space is in reasonable agreement with a previous estimate made for similar shielding by Mewaldt et al [2005].…”
Section: Discussionsupporting
confidence: 88%
“…Applying the modulation model (), we estimate the evolution of dose rates (Figure ). We note that the peak dose rate between cycles 23 and 24 agrees well with the estimate reported recently by Spence et al [], which includes contributions of lunar albedo, of 13.6 cGy/yr. The predictions for both the case of a Gleissberg‐like and Dalton‐like minimum are quite similar.…”
Section: Worsening Hazard From Galactic Radiationsupporting
confidence: 91%
“…We project out to the cycle 24-25 solar minimum and find an elevated dose equivalent rate of ∼0.3 cSv/d in interplanetary space behind 16 g/cm 2 nominal spacecraft shielding or equivalently ∼ 0.15 cSv/d on the lunar surface where roughly half of the incident radiation is blocked by the Moon [Spence et al, 2013]. The estimate for interplanetary space is in reasonable agreement with a previous estimate made for similar shielding by Mewaldt et al [2005].…”
Section: Space Weathersupporting
confidence: 88%
“…In situ measurements of the deep space radiation environment near the LOLA SiAPDs are provided by the CRaTER experiment on the LRO, which measures the effects of ionizing energy loss in matter due to solar energetic particles and galactic cosmic rays [Spence et al, 2010]. Furthermore, we note that though LRO measurements are made near the Moon, which is itself a source of secondary ionizing radiation, Spence et al [2013] showed that greater than 90% of the CRaTER dose is from primary cosmic rays, meaning that results obtained in lunar orbit are excellent proxies for deep space radiation conditions.…”
Section: The Crater Instrumentmentioning
confidence: 99%